OPTIMAL DESIGN OF CRANK BASED ON BOX-BEHNKEN METHOD - CHEN HongWu; TIAN Cheng; PENG CongCong (Jixie qiangdu)
Parametrically building the crank 3D model by Solid Works and doing the FEA by Simulation. Select six parameters and take maximum stress as constraints to solve minimum volume of the structure. Using BBD to optimize the structure and finish 49 iterations. Solid Works can’t fully fit the data. Design the BBD by DOE software Design-Expert and input the simulation data. Then it fits the response surface functions about volume and stress and gets the optimal solution. Comparing with the conclusion of the reference,BBD shows application values on structural optimization.